Aeromonas Flagella (Polar and Lateral) Are Enterocyte Adhesins That Contribute to Biofilm Formation on Surfaces - Kirov, Sylvia M. (American Society for Microbiology, 2004)
Aeromonas spp. (gram-negative, aquatic bacteria which include enteropathogenic strains) have two distinct flagellar systems, namely a polar flagellum for swimming in liquid and multiple lateral flagella for swarming over surfaces. Only ∼60% of mesophilic strains can produce lateral flagella. To evaluate flagellar contributions to Aeromonas intestinal colonization, we compared polar and lateral flagellar mutant strains of a diarrheal isolate of Aeromonas caviae for the ability to adhere to the intestinal cell lines Henle 407 and Caco-2, which have the characteristic features of human intestinal enterocytes. Strains lacking polar flagella were virtually nonadherent to these cell lines, while loss of the lateral flagellum decreased adherence by ∼60% in comparison to the wild-type level. Motility mutants (unable to swim or swarm in agar assays) had adhesion levels of ∼50% of wild-type values, irrespective of their flagellar expression. Flagellar mutant strains were also evaluated for the ability to form biofilms in a borosilicate glass tube model which was optimized for Aeromonas spp. (broth inoculum, with a 16- to 20-h incubation at 37°C). All flagellar mutants showed a decreased ability to form biofilms (at least 30% lower than the wild type). For the chemotactic motility mutant cheA, biofilm formation decreased >80% from the wild-type level. The complementation of flagellar phenotypes (polar flagellar mutants) restored biofilms to wild-type levels. We concluded that both flagellar types are enterocyte adhesins and need to be fully functional for optimal biofilm formation.